Letter: more studies are needed to elucidate the impact of HBV/HCV coinfection on cirrhosis and its consequences—Authors' reply. Issue 4 (17th January 2018) - Pol, S.; Haour, G.; Fontaine, H.; Dorival, C.; Carrat, F.; ,
Abstract : Linked Content This article is linked to Pol et al and Huang et al papers. To view these articles visithttps://doi.org/10.1111/apt.14352 andhttps://doi.org/10.1111/apt.14445 .